2020
DOI: 10.1111/jvh.13341
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal‐associated invariant T‐cells are severely reduced and exhausted in humans with chronic HBV infection

Abstract: Mucosal-associated invariant T (MAIT) cells, defined as CD161 + TCR Vα7.2 + CD3+ T-cells, are a subset of αβ T-cells that possess both innate-and effector-like qualities. 1,2 They are preferentially located in the gut lamina propria and liver 3 and comprise ~1%-10% of the circulating CD3 + T-cells and ~20%-50% of the intrahepatic T-cells in healthy adults. 4,5 MAIT cells play an important role in innate defence against bacterial infections and can be activated by MR1-presented bacterial ligands or by IL-12 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…Previous studies have documented defects in MAIT cell function during infection, cancer and sepsis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Our data showing MAIT cell functional defects directly resulting from TCR stimulation indicates that part of the MAIT dysfunction observed in these settings may result from increased MAIT antigen stimulation, rather than disease-related bystander processes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have documented defects in MAIT cell function during infection, cancer and sepsis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Our data showing MAIT cell functional defects directly resulting from TCR stimulation indicates that part of the MAIT dysfunction observed in these settings may result from increased MAIT antigen stimulation, rather than disease-related bystander processes.…”
Section: Discussionsupporting
confidence: 52%
“…Interestingly, the defect in cytokine production after 5-OP-RU treatment was only observed when the cells were restimulated with 5-OP-RU, and the cells displayed equivalent higher cytokine production as controls upon PMA/ionomycin restimulation, indicating that the defect relates to signaling through the TCR. It is possible that multiple co-inhibitory receptors cooperate in MAIT cell inactivation, as MAIT cells have been shown to express several different immune checkpoint molecules (31, 33, 34, 40, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Another difference between these two studies is the rate of hepatitis B virus (HBV) infection among HCC patients, which was low in the TCGA cohort ( 89 ) and highly prevalent in the cohorts studied by Duan et al ( 20 ). Chronic HBV infection is the most common risk factor for HCC ( 90 ), and has recently been associated with peripheral blood MAIT cell activation and exhaustion although its impact on hepatic MAIT cells is less clear ( 91 93 ). Our pathway enrichment analysis in the HCC scRNA-seq dataset generated by Zheng et al, in which all patients were HBV-positive unlike in the TCGA cohort, revealed the upregulation of antiviral gene modules in tumor-infiltrating MAIT cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that multiple co-inhibitory receptors cooperate in MAIT cell inactivation, as MAIT cells have been shown to express several different immune checkpoint molecules. 32 , 34 , 35 , 41 , 42 …”
Section: Discussionmentioning
confidence: 99%